Distinct Electrocardiographic Form of Idiopathic Ventricular Arrhythmia Originating From the Left Bundle Branch. (23rd September 2016) - PATHAK, RAJEEV K.; BETENSKY, BRIAN P.; SANTANGELI, PASQUALE; DIXIT, SANJAY
Distinct Electrocardiographic Form of Idiopathic VA: Most premature ventricular contractions (PVCs) arise from the right or left ventricular outflow tract. Some VPCs originate near the His‐bundle region. However, there remains a paucity of information on PVCs originating directly from the cardiac conduction system. We describe 2 cases with idiopathic frequent PVCs that were mapped directly to the left bundle branch itself. We also provide an anatomic‐based mapping and ablation approach for management of these uncommon and challenging arrhythmias. In both cases we were able to either eliminate or significantly suppress the ectopic source by applying radiofrequency at this location without causing any significant impairment of the atrioventricular conduction.